Preventing opioid overdose with peer-administered naloxone: findings from a rural state - Bridget L. Hanson; Rebecca R. Porter; Amanda L. Zöld; Heather Terhorst-Miller (BMC, 2020)
Abstract Background In response to the opioid epidemic, naloxone distribution programs aim to prevent overdose death by making naloxone available and training people to use it. Peers of individuals at risk of opioid overdose are well-positioned to administer naloxone and prevent overdose death. Methods We conducted key informant interviews with 18 individuals with past or current opioid and heroin drug use who had administered naloxone to a peer during an overdose emergency. Interviews explored individuals' experiences with administration and their recommendations for program and policy improvement. Data were systematically coded and analyzed for themes. Results Participants sought naloxone rescue kits because they perceived high risk of overdose. They described high satisfaction with training and felt prepared to administer naloxone during overdose incidents. Overwhelmingly, participants perceived naloxone to be effective and emphasized the need to make it widely available. Findings suggest that engagement in overdose prevention strategies other than naloxone differs by gender, with females more likely than males to use multiple different strategies. Participants described that overdose experiences do not have a lasting impact on drug use behaviors. Conclusions Findings support the feasibility of naloxone distribution to peer opioid and heroin users and provide recommendations for policy improvement, including effective and well-advertised Good Samaritan laws and links to treatment for opioid use disorder.